LEARNING MATHEMATICS THROUGH THE APPLICATION OF AUGMENTED REALITY (AR) TECHNOLOGY MEDIA - Romadloni, Dewi Khosyatillah; Yunita, Elin Herlina; Auliyah, Hoda; Solehah, Mar’ahtu; Rasilah, Rasilah (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Augmented Reality (AR) has emerged as an important innovation in education, especially in mathematics learning. The purpose of writing this article is to determine the application of AR technology media in mathematics learning. The research method in this article is systematic literature, this research highlights the positive impact of AR on student engagement, conceptual understanding, and learning outcomes. AR enables interactive visualizations that help students overcome barriers in understanding mathematical concepts. The results of this research found that AR increases student interest and encourages a more interactive learning environment. Apart from that, AR-based learning media has high validity, practicality and effectiveness. AR is not only suitable for one level of education but can also be applied at various levels, from elementary to middle school. Positive responses from students reinforce that AR is a feasible and practical tool to use in mathematics learning. Thus, AR shows great potential to transform mathematics learning in the digital era, helping students better understand complex concepts and increasing their engagement in the learning process.